2009
DOI: 10.1371/journal.pone.0004387
|View full text |Cite
|
Sign up to set email alerts
|

Empathy Is Moderated by Genetic Background in Mice

Abstract: Empathy, as originally defined, refers to an emotional experience that is shared among individuals. When discomfort or alarm is detected in another, a variety of behavioral responses can follow, including greater levels of nurturing, consolation or increased vigilance towards a threat. Moreover, changes in systemic physiology often accompany the recognition of distressed states in others. Employing a mouse model of cue-conditioned fear, we asked whether exposure to conspecific distress influences how a mouse s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
203
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(215 citation statements)
references
References 38 publications
6
203
0
1
Order By: Relevance
“…Previous studies have shown that exposure to distressed conspecific in rodents acts as unconditional stimulus (US) in both contextual and cued fear conditioning (Chen et al, 2009;Jeon et al, 2010;Yusufishaq and Rosenkranz, 2013) and enhances active avoidance learning performed in a different context immediately after the exposure (Knapska et al, 2010). Here we found enhanced PA learning 24 h after OF, which implies lasting modifications of the fear learning circuits.…”
Section: Psychological Trauma and Fear Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that exposure to distressed conspecific in rodents acts as unconditional stimulus (US) in both contextual and cued fear conditioning (Chen et al, 2009;Jeon et al, 2010;Yusufishaq and Rosenkranz, 2013) and enhances active avoidance learning performed in a different context immediately after the exposure (Knapska et al, 2010). Here we found enhanced PA learning 24 h after OF, which implies lasting modifications of the fear learning circuits.…”
Section: Psychological Trauma and Fear Memorymentioning
confidence: 99%
“…Such exposures interrupt ongoing activities (Church, 1959), increase depression and anxiety-like behaviors (Warren et al, 2013), and elicit fear learning (Chen et al, 2009;Jeon et al, 2010;Yusufishaq and Rosenkranz, 2013). Emotionally salient stimuli generally recruit the dorsomedial prefrontal cortex (dmPFC) and the basolateral amygdala (BLA), which have strong reciprocal projections (Hubner et al, 2014;McDonald, 1998) and are involved in fear learning (Gilmartin et al, 2014;Marek et al, 2013;Senn et al, 2014), including contextual learning during observational fear (Amano et al, 2010;Jeon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Probably, this mechanism is a mammalian universal, given that part of its assumed neural underpinnings were first discovered in macaques (e.g. mirror neurons; Rizzolatti et al 1996) and that emotional contagion (often considered the starting point of empathy) is increasingly studied in rodents (Langford et al 2006;Chen et al 2009;Grenier & Lü thi 2010). Mirroring mechanisms permit one individual to resonate with the emotional state of another, thus priming this individual for actions appropriate to the other's state, such as when a mother is distressed at hearing the distress calls of her young resulting in comforting behaviour (Panksepp 1996).…”
Section: Introductionmentioning
confidence: 99%
“…An example is an experiment with mice where one mouse (temporally called "A") observes another mouse receiving an electric shock accompanied by a tone. Eventually, A freezes in response to the tone even though A has never experienced the shock [8]. Here, A's freezing behavior is triggered by its emotional reaction and might be interpreted as a sign of emotional contagion.…”
Section: Emotional Contagionmentioning
confidence: 99%